Coronary Calcium Scanning in Patients after Adjuvant Radiation for Early Breast Cancer and Ductal Carcinoma In situ - Chang, Monique; Suh, Jason; Kirtani, Vatsala; Dobrescu, Andrei; Haas, Jonathan; Zeldis, Steven; Shayani, Steven; Hindenburg, Alexander A. (Frontiers in Oncology, 2013)
Background and Objective Radiation therapy (RT) is part of standard adjuvant treatment for breast cancer. Earlier studies demonstrated increased cardiac morbidity and mortality from this. Coronary Calcium scanning utilizing Multidetector Computed Tomography (MDCT) can detect early atherosclerosis in coronary arteries by identifying the amount of calcifications. In our study we employed these tools to detect occult atherosclerosis at least 5 years following breast RT. Methods We evaluated 20 asymptomatic patients, less than 60 years old, treated with RT at least 5 years prior to enrollment. 9 received RT to the left and 11 to the right chest wall. The median interval between RT and calcium scan was 8 years. All patients were treated with external beam RT using tangential technique. All patients underwent MDCT to compute volumetric and Agatston calcium scores of the coronary arteries and the aorta. Results 11 patients had RT to the right chest wall, and 8 had a calcium score of 0, while 2 had minimally elevated scores and 1 patient had a significantly elevated score. Meanwhile 9 patients had RT to the left chest wall, and 7 had a calcium score of 0. None had significantly elevated scores. In the aorta, 11 of 20 patients had a score of 0, while 8 of 20 had minimally elevated scores. Conclusions In contrast to studies demonstrating increased cardiovascular morbidity, our pilot study did not detect significant occult atherosclerosis using MDCT of the coronaries and aorta of patients assessed five or more years following radiation for treatment of breast cancer.